The impact of a child being diagnosed with T1DM on their family’s dietary habits - Karaiskou, Avgi; Resta, Maria; Dimitriadou, Meropi; Pappa, Konstantina; Triantafyllou, Panagiota; Christoforidis, Athanasios (Progress in Nutrition, 2020)
Despite the well-known effects of Type 1 Diabetes Mellitus (T1DM) diagnosis on a child’s alimentation and their family’s relationship and psychology, its impact on the whole family’s dietary habits has not been adequately investigated. This study’s objective is to delve into this less explored subject. Our study’s sample consisted of fifty families with a child diagnosed with T1DM, who were evaluated via two questionnaires, the widely used FEAH questionnaire and a second one that we developed for the purposes of this study. Mothers and especially those with children diagnosed with T1DM at an early age changed their dietary habits in a higher proportion Our study found no correlation between changing one’s eating pattern and their educational or socio-economic status. A significant number of families retained their unhealthy nutritional habits after the diagnosis of T1DM and in conjunction with the reported low level of physical activity indicate areas for intervention.